Impact of Water Management on Local Potential Evolutions during PEM Fuel Cell Operation with Dead-Ended Anode. (14th September 2015) - Abbou, Sofyane; Dillet, Jérôme; Maranzana, Gael; Didierjean, Sophie; Lottin, Olivier
Abstract : Operating a PEMFC with a dead-ended anode may lead to local fuel-starvation because of water and possibly nitrogen accumulation in the anode compartment. In previous works, we used a segmented linear cell with reference electrodes to monitor simultaneously the local potentials and current densities during dead-ended anode operation. The results indicated that water transport as well as nitrogen crossover through the membrane were most probably the two key factors governing fuel starvation. In this work, we evaluated with more details the contributions of nitrogen crossover and water transport to hydrogen starvation by using different cooling temperature on the cathode and anode sides. The results show that with a colder anode side, fuel-starvation was faster. In the opposite case of a hotter anode plate, water accumulation in the anode compartment was limited, suggesting that nitrogen crossover through the membrane was probably the main reason for hydrogen starvation in this case while water it is water in regular operation (i.e., with identical cooling temperature on both sides).